The Importance of Managing Context and Moving Objects Data for Emergency Management System - Kamal Baharin, S. S.; Suryana, N. (2007)
During emergencies, time is critical at all levels and requires efficient management of data and communication flow. When disaster strikes various agencies get involved. These organizations require timely interaction and diverse, detailed information to coordination of public emergency services in order to save lives and property. However effectiveness of emergency management depends on the data that come from various resources and format, and effectiveness of communication flow depends on the integration between and within various organizations and scheduling assigned by each frontline of organization personnel. Today, database technology is used in this field but still could be extent to tremendous potential for increasing the efficiency and effectiveness in coping with disaster situation. In this paper we outline the ubiquitous computing technology to be integrated in disaster management information and communication system in order to enhance in data management and scheduling issues during the response phase of disaster lifecycle.